2009
DOI: 10.1002/mds.22596
|View full text |Cite
|
Sign up to set email alerts
|

Intrajejunal levodopa infusion in Parkinson's disease: A pilot multicenter study of effects on nonmotor symptoms and quality of life

Abstract: Switching from oral medications to continuous infusion of levodopa/carbidopa gel reduces motor complications in advanced Parkinson's disease (PD), but effects on nonmotor symptoms (NMSs) are unknown. In this prospective open-label observational study, we report the effects of intrajejunal levodopa/carbidopa gel infusion on NMS in PD based on standard assessments utilizing the nonmotor symptoms scale (NMSS) along with the unified Parkinson's disease rating scale (UPDRS 3 motor and 4 complications) and quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
171
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(199 citation statements)
references
References 35 publications
18
171
1
9
Order By: Relevance
“…37,48 Non-motor symptoms are likely to significantly affect QoL and several such symptoms were improved by LCIG in a six-month study. 41 Cognitive function was reported to be improved in two patients, two to 24 months after the introduction of LCIG, possibly related to increased 'on' time. 49 In an interview with 25 patients, of whom the majority had been using infusion for more than two years, 76 % agreed completely that their QoL was improved with infusion as compared to before.…”
Section: Long-term Efficacy With Levodopa/carbidopa Intestinal Gel Inmentioning
confidence: 91%
See 1 more Smart Citation
“…37,48 Non-motor symptoms are likely to significantly affect QoL and several such symptoms were improved by LCIG in a six-month study. 41 Cognitive function was reported to be improved in two patients, two to 24 months after the introduction of LCIG, possibly related to increased 'on' time. 49 In an interview with 25 patients, of whom the majority had been using infusion for more than two years, 76 % agreed completely that their QoL was improved with infusion as compared to before.…”
Section: Long-term Efficacy With Levodopa/carbidopa Intestinal Gel Inmentioning
confidence: 91%
“…12,13,[35][36][37][38][39][40][41][42][43][44][45][46] Most studies so far have focused on motor symptoms. The general finding is that LCIG provides more time in motor states near normal performance and less time in 'off' and dyskinetic states as compared to conventional optimised therapy.…”
Section: Long-term Efficacy With Levodopa/carbidopa Intestinal Gel Inmentioning
confidence: 99%
“…Similarly, another retrospective study [66] showed the safety and tolerability of 24-h infusion of LCIG on 21 advanced PD patients with severe night-time disability, the drop-out rate from treatment due to worsening of cognitive/neuropsychiatric symptoms being <5%. Sanchez Castaneda et al [67] described the marked improvement of cognitive functions after switching oral therapy to LCIG infusion in two patients with PD with cognitive impairment, and Honig and coworkers [68] demonstrated the significant beneficial effect of LCIG on NMS, in particular attention and memory, in an observational study on 22 advanced PD patients monitored for 6 months. Finally, Zibetti and collaborators [69] performed a prospective study on 25 patients treated with LCIG for 3 years.…”
Section: Continuous Dopaminergic Stimulation In the Advanced Stages Omentioning
confidence: 99%
“…With a constant infusion rate of the levodopa-carbidopa gel during the waking hours, smooth plasma levodopa levels, and therefore, more continuous stimulation of striatal dopamine receptors can be achieved. This has been shown to be a successful strategy to minimize motor fluctuations and dyskinesias in advanced PD patients, in addition to providing a more consistent clinical benefit [42,61] and enhanced quality of life (QoL) [62,63].…”
Section: Continuous Duodenal Levodopa Infusionmentioning
confidence: 99%